Increasing The Availability of Manure with Automatic Manure Mixer and Refining Media in Sukodono Village, Sidoarjo - Novianti, Triuli; Kurniawati, Indah; Winarno, Winarno; Reynanda Bagus Widya Astomo; Rudi Irmawanto (Kontribusia : Research Dissemination for Community Development, 2025)
In everyday life, the process of making manure manually requires a longer time and extra effort. This is an obstacle for farmers to increase the availability of organic fertilizers as a mixture in the fertilization process of plants. Therefore, a breakthrough is needed so that farmers can increase the availability of organic fertilizers. One of the areas where farmers need to increase the availability of organic fertilizers is farmers in RT 09 RW 03 Sukodono Village, Sidoarjo Regency. In January 2024, mentoring activities will be carried out to increase the availability of organic fertilizers. Some innovations that can be done are by using a fertilizer mixer and smoother with the main drive being an electric motor because electric motors have several advantages that motors with internal combustion do not have, such as electric motors are very easy to control and operate, have good durability, are environmentally friendly, and save energy. This tool uses an electric motor with a direct current motor type at a working voltage of 24 Volts equipped with a planetary gearbox applied to manure-making equipment. This service activity has been carried out well, and the farmers of RT 09 RW 03 Sukodono Village, Sidoarjo Regency can apply this tool optimally to increase the availability of organic fertilizers.